2012
DOI: 10.1200/jco.2012.30.4_suppl.368
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prediction of venous thromboembolism (VTE) in ambulatory patients (pts) with pancreas cancer receiving chemotherapy.

Abstract: 368 Background: VTE is considered a main cause of mortality and morbidity in cancer pts and is commonly underestimated by oncologists. Pancreatic cancer is associated with the highest risk of VTE and the true incidence remains uncertain. Chemotherapy has been identified as an independent risk factor for VTE. The aim of this study is to analyze the incidence of cancer-associated thrombosis in ambulatory pts with pancreatic cancer receiving chemotherapy. Methods: We performed a retrospective review to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The placebo-controlled ENOXACAN II trial included 332 patients undergoing elective open surgery for abdominal or pelvic cancer, and was randomized between thromboprophylaxis for 6-10 days or an additional 21 days. This study also showed that an extended duration of enoxaparin prophylaxis was safe and reduced the incidence of VTE by 60% (95% CI [10][11][12][13][14][15][16][17][18][19][20][21][22]42,[42][43][44][45][46][47][48][49][50][50][51][52][53][54][55][55][56][57][58][59][60][61][62][63][64][65][66]68,[72][73][74][75][76][77]…”
Section: Postoperative Thromboprophylaxis In Patients With Resectable...mentioning
confidence: 70%
See 1 more Smart Citation
“…The placebo-controlled ENOXACAN II trial included 332 patients undergoing elective open surgery for abdominal or pelvic cancer, and was randomized between thromboprophylaxis for 6-10 days or an additional 21 days. This study also showed that an extended duration of enoxaparin prophylaxis was safe and reduced the incidence of VTE by 60% (95% CI [10][11][12][13][14][15][16][17][18][19][20][21][22]42,[42][43][44][45][46][47][48][49][50][50][51][52][53][54][55][55][56][57][58][59][60][61][62][63][64][65][66]68,[72][73][74][75][76][77]…”
Section: Postoperative Thromboprophylaxis In Patients With Resectable...mentioning
confidence: 70%
“…Treatment with antineoplastic agents has been associated with an increased VTE risk in patients with all-type cancer [47][48][49][50]. In patients with PDAC, chemotherapy as the first-line cancer treatment is associated with an increased VTE incidence [22,51]. Withinthe neoadjuvant setting, patients with borderline resectable and locally advanced PDAC are commonly treated with FOLFIRINOX chemotherapy or gemcitabine-based chemoradiation in borderline resectable PDAC [4,52,53].…”
Section: Pdac-treatment-related Risk Factorsmentioning
confidence: 99%